Combined subsoiling and ridge–furrow rainfall harvesting during the summer fallow season improves wheat yield, water and nutrient use efficiency, and quality and reduces soil nitrate-N residue in the dryland summer fallow–winter wheat rotation - Wu, Jinzhi; Wang, Rongrong; Zhao, Wenxin; Zhao, Kainan; Wu, Shanwei; Zhang, Jun; Wang, Hezheng; Fu, Guozhan; Huang, Ming; Li, Youjun (Frontiers in Plant Science, 2024)
Both subsoiling tillage (ST) and ridge and furrow rainfall harvesting (RF) are widely implemented and play an important role in boosting wheat productivity. However, information about the effects of ST coupled with RF during the summer fallow season on wheat productivity and environmental issues remain limited. This study aims to explore the effects of ST coupled with RF on the water harvesting, wheat productivity-yield traits, water and nutrient use efficiency and quality, and soil nitrate-N residue in dryland winter wheat-summer fallow rotation at the intersection of southern Loess Plateau and western Huang-Huai-Hai Plain in China in 2018-2022. Three tillage practices-deep plowing with straw turnover (PTST), subsoiling with straw mulching (STSM) and STSM coupled with RF (SRFSM) are conducted during summer fallow season. The results indicated that tillage practices during the summer fallow season significantly impacted wheat productivity and soil nitrate-N residue. Compared to PTST, STSM significantly enhanced rainfall fallow efficiency and water use efficiency by 7.0%and 14.2%, respectively, as well as N, P and K uptake efficiency by 16.9%, 16.2% and 15.3%, thus increased grain yield by 14.3% and improving the most parameters of protein components and processing quality, albeit with an increase in nitrate-N residue in 0-300 cm soil depth by 12.5%. SRFSM, in turn, led to a further increase in water storage at sowing, resulting in an increase of water use efficiency by 6.8%, as well as N, P and K uptake efficiency and K internal efficiency by 11.8%, 10.4%, 8.8%, and 4.7%, thereby significantly promoting grain yield by 10.2%, and improving the contents of all the protein components and enhancing the processing quality in grain, and simultaneously reducing the nitrate-N residue in 0-300 cm soil layer by 16.1%, compared to STSM. In essence, this study posits that employing subsoiling coupled with ridge-furrow rainfall harvesting (SRFSM) during the summer fallow season is a promising strategy for enhancing wheat yield, efficiency, quality, and simultaneously reducing soil nitrate-N residue within dryland summer fallow-winter wheat rotation system.